The Impact of Increasing Performance and Productivity in the Management of Human Resources in Albanian Enterprises - VELA, Fioralba; SINAJ, Zamira (Theoretical and Practical Research in Economic Fields; Vol 14 No 1 (2023): TPREF, Volume XIV, Issue 1(27), Summer 2023, 2023)
The importance of improving the efficiency of enterprises in Albania and, consequently, the role of personnel management in the implementation of this task has increased especially in recent years when the number of workers has decreased significantly due to the increase in emigration. The purpose of the study is to determine the most effective system of motivation and planning for them, considering the characteristics and national mentality of agricultural workers, and to form recommendations for the most acceptable management style for this group. The Holfstede typology of cultural dimensions was used as a primary method to identify the cultural and behavioral characteristics of the target audience. As a result of the survey conducted among 1514 staff representatives and the processing of its results, the average indicators for cultural dimensions were calculated and the evaluations of these indicators were given. According to the data obtained for the typology of cultural dimensions, it was found that the values in the examined social group are mainly determined by traditions and customs, which means that a management model is required that will not impose the existing principles of Western management but uses the tools own based on relatively democratic principles. Based on the obtained characteristics, recommendations were formed for such main management tools as the principles of subordination, the system of defining tasks and monitoring their implementation, as well as for effective motivation of personnel. The practical importance of the study lies in the development of recommendations for improving personnel management and, as a result, increasing efficiency in agricultural enterprises in Albania.